PEMEROLEHAN KALIMAT BAHASA INDONESIA ANAK USIA LIMA TAHUN - Haeriyah Novita (Universitas Lambung Mangkurat, 2018)
AbstractAcquisition is a process of mastery of language done by children naturally when he learned the firstlanguage or his mother tongue. In this case, there are two processes that occur in it, namely the acquisitionof language and language learning. Thus, language acquisition is concerned with the first language, whilelanguage learning is concerned with a second language. This study aims to describe the acquisition ofphrases and sentences of Indonesian children aged five years.This research uses a qualitative approachwith descriptive research type of analysis. All data obtained from the speech of a five-year-old childas a source of data. Techniques refer libat proficient, recording techniques, and techniques record is atechnique used by the author to collect data in this study.The results of this study found variations ofphrases and sentences. The phrase in question is a phrase consisting of a nominal phrase, a verbal phrase,a numeral phrase, an adverbial phrase, a preposition phrase, and an adjective phrase. In addition, thefive-year-old also has sentences consisting of core sentences and non-core sentences, single sentences andcompound sentences, major sentences and minor sentences, verbal sentences and non-verbal sentences,as well as free and bound sentences.Thus, the results of this study can be used as one of the comparativematerials with subsequent studies that will examine the acquisition of Indonesian sentence of five-yearoldchild although the aspects studied vary.Key words: earnings, sentences, children five yearsAbstrakPemerolehan Kalimat Bahasa Indonesia Anak Usia Lima Tahun. Pemerolehan merupakan prosespenguasaan bahasa yang dilakukan oleh anak secara natural pada waktu ia belajar bahasa pertamaatau bahasa ibunya. Dalam hal ini, terdapat dua proses yang terjadi di dalamnya, yakni pemerolehanbahasa dan pembelajaran bahasa. Jadi, pemerolehan bahasa berkenaan dengan bahasa pertama,sedangkan pembelajaran. Penelitian ini bertujuan mendeskripsikan pemerolehan frasa dan kalimatbahasa Indonesia anak usia lima tahun. Penelitian ini menggunakan pendekatan kualitatif denganjenispenelitian deskriptif analisis. Seluruh data yang didapatkan dari ujaran-ujaran anak usia lima tahunsebagai sumber data. Teknik simak libat cakap, teknik rekam, dan teknik catat merupakan teknik yangdigunakan penulis untuk mengumpulkan data dalam penelitian ini.Hasil penelitian ini ditemukannyabentuk-bentuk frasa dan kalimat yang bervariasi. Frasa yang dimaksud adalah frasa yang terdiri darifrasa nominal, frasa verbal, frasa numeral, frasa adverbial, frasa preposisi, dan frasa adjektival. Selainitu anak usia lima tahun tersebut juga sudah memperoleh kalimat yang terdiri dari kalimat inti dankalimat non-inti, kalimat tunggal dan kalimat majemuk, kalimat mayor dan kalimat minor, kalimat246verbal dan kalimat non-verbal, serta kalimat bebas dan terikat. Dengan demikian, hasil penelitian inidapat dijadikan salah satu bahan pembanding dengan penelitian-penelitian selanjutnya yang akanmengkaji tentang pemerolehan kalimat bahasa Indonesia anak usia lima tahun walaupun dengan aspekyang dikaji berbeda-beda.